2013
DOI: 10.5125/jkaoms.2013.39.3.103
|View full text |Cite
|
Sign up to set email alerts
|

Tooth-derived bone graft material

Abstract: With successful extraction of growth factors and bone morphogenic proteins (BMPs) from mammalian teeth, many researchers have supported development of a bone substitute using tooth-derived substances. Some studies have also expanded the potential use of teeth as a carrier for growth factors and stem cells. A broad overview of the published findings with regard to tooth-derived regenerative tissue engineering technique is outlined. Considering more than 100 published papers, our team has developed the protocols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
137
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(162 citation statements)
references
References 78 publications
0
137
0
Order By: Relevance
“…It is known that the composition of DDM is similar to that of the autogenous bone in terms of the proportion of inorganic (65%) and organic (35%) substances 6,7) . Experiments, such as the Bradford assay, for assessing the organic composition of DDM suggested that the osteoinductivity of DDM was sufficient for new bone formation 12,34) . Among the organic components, DDM is composed at 90% of type I collagen and 10% of noncollagenous proteins, including osteocalcin, osteopontin, osterix, Runx2, phosphophoryn, and sialoprotein 34) , which are less represented in Bio-Oss Collagen ® and could partially explain the higher osteogenic potential of the DDM in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the composition of DDM is similar to that of the autogenous bone in terms of the proportion of inorganic (65%) and organic (35%) substances 6,7) . Experiments, such as the Bradford assay, for assessing the organic composition of DDM suggested that the osteoinductivity of DDM was sufficient for new bone formation 12,34) . Among the organic components, DDM is composed at 90% of type I collagen and 10% of noncollagenous proteins, including osteocalcin, osteopontin, osterix, Runx2, phosphophoryn, and sialoprotein 34) , which are less represented in Bio-Oss Collagen ® and could partially explain the higher osteogenic potential of the DDM in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Since the development of tooth-derived bone grafting materials, reports showed that the physicochemical characteristics of autogenous demineralized dentin matrix (DDM) were similar to those of autogenous cortical bone [5][6][7][8] . Owing to this advantage, bone grafting materials from the autogenous tooth have been used actively, and their clinical applications were approved 6,[9][10][11][12][13][14][15][16] . Recently, a 5-year-long followup of DDM based on cone-beam computed tomography evaluation showed s uccessful guided bo n e regen erati on with ou t complications 17) .…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, an autogenous bone graft material was developed from extracted teeth, and subjected to many basic and clinical studies. It has since been found to be an excellent biocompatible material with osteoinductive and osteoconductive potential [5][6][7][8]15,16) . Researches that demineralized dentin matrix (DDM) can play a role as the scaffold of bone morphogenic protein (BMP) and growth factors were announced.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical effectiveness of autogenous tooth bone graft, which was domestically developed in 2008 and now being actively used, was already proved. Also, it was reported that it showed the similar healing state to free autogenous bone graft as its osteoconductive and osteoinductive healing were excellent and bone remodeling was good [5][6][7] . Meanwhile, although tissue engineering research using various growth factors, bone morphogenic protein, and stem cell, etc is actively being performed worldwide, the appropriate scaffold to carry them have not been developed much.…”
Section: Introductionmentioning
confidence: 99%
“…Bone morphogenic proteins have long been utilized in scaffolds as stimulants for a hastened growth of bone matrix and cartilage [40]. Presently, the transfection of genetic factors to cellular populations in scaffolds, namely PDLSCs, resulted in an escalation of PDGF, with greater cementoblastic activity than reported in recombinant PDGF delivery [41].…”
Section: Genetic and Nutritive Regulationmentioning
confidence: 99%